Diagnosis of Helicobacter pylori in cholelithiasis and cholecystitis: by histology and serological association - Doraiswamy, Srinivasan; Kumar, Dharmendra; Sreeramulu, P. N.; ., Suresh (International Surgery Journal, 2019)
Background: Biliary calculus disease is one of the most common disorders affecting the gastrointestinal tract. It is an important cause of morbidity. There has been marked rise in the incidence of gall stone disease in the west. In India, it is more common in northern states than in South India. Incidence of gallstones increases with age with a male to female ratio of 1:4. About 50% of these patients are asymptomatic. Methods: An analytical prospective study on patients diagnosed with cholecystitis and/or cholelithiasis was conducted in R. L. Jalappa Hospital Tamaka, Kolar. 58 patients were included in the study between June 2018 and May 2019. Data was collected and analysed using SPSS 22 version software. Categorical data was represented in the form of frequencies and proportions. Results: The age incidence was found to be highest between 31 to 40 years. The incidence of cholelithiasis was more in females. All patients presented with pain abdomen. Calculous cholecystitis was the most common mode of presentation. Open cholecystectomy was commonly done for cholelithiasis in our set up. Chronic calculous cholecystitis is the commonest histopathology. Conclusions: According to our findings evidence of recent and chronic infection Helicobacter pylori as shown by demonstration of IgM and IgG class of antibodies respectively to the organism was found in most of patients and histological evidence of the patients with cholecystitis and cholelithiasis. Thus, the frequency of helicobacter infection seems to be low in the patient population studied.